PENTINGNYA PENDIRIAN LEMBAGA PEMASYARAKATAN KHUSUS WANITA DI DAERAH ISTIMEWA YOGYAKARTA - , YUSTIN VERINA IP ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Gender-based violence is a serious problem that is being faced by today's women and it is also possible to override the female inmates that must be met from the system that overshadowed them, in this case the prison, so the writers do the writing reflection on the conditions surrounding the rights prisoners associated with the fulfillment of the needs of women have a special correctional institutions, especially in DIY. The purpose of the implementation of the Job Practice for the write r is to give real experience to students as candidates for professional workers in order to bridge the gap between theory learned during lectures profession and practice of the profession in the real world of work, as well as to provide real work experienc e to the author prior to entering the workforce. Given the condition of women prisoners are vulnerable to human rights violations during serving his sentence in a correctional institution , associated with meeting the needs of women have special prisons , particularly in the area of DIY to date in the Special Province of Yogyakarta also has not had a women's Correctional Facility. Especially to see how far the government meets DIY embodiment of law and human rights friendly and humanist who could become part of the embodiment RANHAM real and concrete areas on the idea of the establishment of Special Prison for Women as soon as possible separate female inmates at a different place to minimize the potential - potential human rights violations against women inmates . As well as instruments to ensure legal protection for inmates defined in Article 3 paragraph ( 2 ) of Act 39 of 1999 on Human Rights , that " every person has the right to recognition, security , protection and fair treatment before the law and obtain legal certainty and treatment equal before the law .